Fish fauna and water quality of Batang Lemanak : effects of logging and its implications towards riverine fish management - Lee, Wei Wei. (Universiti Malaysia Sarawak (UNIMAS), 2004)
This study was conducted to determine the diversity of fish communities in Batang Lemanak and the effects of changes in aquatic environment especially the effects of increasing suspended solid (TSS) towards the freshwater fish species. TSS loading was calculated based on the river hydrology. Another seven water quality parameters, namely DO, BOD, temperature, pH, N03-·N, pol and NH3-N were used to determine the quality of the river water. River water was sampled from the main river and its tributaries for comparison purposes. The results showed the degradation of water quality at the stations which had been affected by the logging activities. Statistical analysis showed that the water temperature was not significantly different among the stations but there were significant differences between first sampling and second sampling. The distribution and population offish species was also affected due to the changes of habitat.